Household-level food and nutrition insecurity and its determinants in eastern India - Parappurathu, Shinoj; Kumar, Anjani; Bantilan, Cynthia; Joshi, Pramod Kumar (2019)
Past studies have reported serious levels of food insecurity and under-nutrition existing in the eastern belt of India. This study specifically examined the food consumption pattern, levels of nutrition intake and nutrient intake gap of sample households in 12 villages of Eastern India based on data collected during the agricultural year 2011–12. The results point to serious levels of nutrient intake deficit in the sample villages, though with notable disparities in its level of incidence. Major socio-economic and demographic variables that determine the calorie deficit status of the households were identified, the knowledge of which is important while planning interventions.